TECHNIQUE OF ZEOLITE APPLICATION ON AGRICULTURAL AS A SOIL AMELIORANT - Suwardi Suwardi (Jurnal Zeolit Indonesia, 2009)
Indonesia is one of countries which is rich in zeolite deposits. Volcanic activities in this country millions years ago released much of volcanic tuff as source of zeolite materials. The most important of zeolite characteristics are high cation exchange capacity (CEC), capability to absorb ammonium ions, and their unique porous structures. Those characteristics can be used for many utilities of zeolite for agriculture such as soil ameliorant, slow release agent of nitrogen fertilizer, and growth media of horticultural plants. Application of zeolite as soil ameliorant gave good effect if applied in low CEC soil such as Oxisol, Ultisol, and some Inceptisol with high dossage of 10-15 ton/ha. Although zeolites improved the soil characteristics and crop production, only a few farmers used zeolites due to economical reasons. Therefore, other techniques should be developed for stimulating farmers to use zeolites. Application of zeolite with lower dosage can be mixed directly with urea in ratio of 1:1 or 30% if the mixtures are pelletized. Zeolite can be applied in company with other soil ameliorants such as compost, liming, and humic acid.